Challenges to traditional management of connected ecosystems within a fractured regulatory landscape: A case study from southern New Zealand. Issue 9 (24th June 2019) - Hepburn, Christopher D.; Jackson, Anne‐Marie; Pritchard, Daniel W.; Scott, Nigel; Vanderburg, Patricia H.; Flack, Brendan
Abstract: Indigenous people often manage natural environments and resources based on landscape features. Rights and management responsibilities that follow pathways of water from their source in alpine areas down and ultimately into and out to sea are common. Contemporary frameworks that seek to support management of the environment, ecosystems and resources from marine areas to alpine zones are not so connected. The East Otago Taiāpure and Waikouaiti Mātaitai are Customary Protection Areas (CPAs) that connect from fresh water into the marine environment. These CPAs fall within the cultural landscape of Kāti Huirapa ki Puketeraki, the hapū (sub‐tribe) of Ngāi Tahu, the iwi (tribe) who holds mana whenua (authority) over East Otago. CPAs may provide a way for iwi and hapū to manage a catchment as a whole, and to allow for traditional approaches to management within a contemporary legislative framework. Despite local successes in restoring habitat, changing legislation, gaining knowledge and building community support for change, fundamental issues remain. Members of the East Otago Taiāpure Committee reflect on the last 15 years of management and identify constraints and enablers of community‐led management across inherently connected ecosystems using a kaupapa Māori approach. A compartmentalized view of connected ecosystems, complex legislation and government‐focused processes emerge as issues that make even seemingly simple issues complicated for community managers. If locally led management models are to work, continuity of the relationships between government agencies and the community, an understanding of the long‐term and connected view of community groups, resourcing and support beyond the issue of the day, and clear pathways to affect change are key. For true community‐led ecosystem management to be effective, we must focus on the needs and the perspectives of the community and move away from structures designed to ease the role of government in managing natural resources and the environment.